1996
DOI: 10.1007/s003359900245
|View full text |Cite
|
Sign up to set email alerts
|

Synteny mapping in river buffalo

Abstract: The cosegregation of ten coding loci has been investigated, in a panel of 37 somatic cell hybrids resulting from the fusion of a hamster cell line and river buffalo lymphocytes, by use of Southern hybridization technique. Five syntenic groups, TCRB-PGY3, ASS-ABL, FUCA1P-CRYG, MBP-YES1, and CGN1-ACTA1, previously assigned to cattle as U13, U16, U17, U28, and U29 respectively, were also found to be syntenic in buffalo. Based on the extensive syntenic conservation and banding homology between cattle and river buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The present study confirms syntenic conservation between cattle and buffalo as previously demonstrated [6,7,11,32]. Chromosomal conservation between cattle and buffalo has also been demonstrated, based on the banding homoeology between cattle and river buffalo chromosomes [22].…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The present study confirms syntenic conservation between cattle and buffalo as previously demonstrated [6,7,11,32]. Chromosomal conservation between cattle and buffalo has also been demonstrated, based on the banding homoeology between cattle and river buffalo chromosomes [22].…”
Section: Methodssupporting
confidence: 74%
“…Therefore, inferences can be made concerning the expected location of markers in one species from information available in another species. Several genes previously assigned to cattle syntenic groups and/or chromosomes have been assigned to buffalo chromosomes [6,7,10,11,18,19,23,24,28].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies and this latest map, all buffalo chromosome arms have homology to single bovine acrocentric chromosomes. Buffalo (BBU) chromosome 1 appears to be a fusion of Bos taurus (BTA) chromosome 1 and 27, BBU2 equals BTA2 and 23,BBU3 equals BTA8 and 19,BBU4 equals BTA5 and 28,and BBU5 equals BTA16 and 29 at the cytogenetic level with state of the art banding (El Nahas et al, 1996, 2001Iannuzzi et al, 2003). All the other chromosomes have a one-to-one correspondence between the two species.…”
mentioning
confidence: 99%
“…ZOO-FISH studies using human chromosome paints have been reported in such domestic animals as cattle (Hayes, 1995;Solinas-Toldo et al, 1995;Chowdhary et al, 1996), pig Rettenberger et al, 1995), horse (Raudsepp et al, 1996), and cat (O'Brien et al, 1997), but they are still lacking in other economically important domestic species, such as the river buffalo, where only a few loci have been physically mapped using both somatic cell hybrid (El Nahas et al, 1996;De Hondt et al, 1997) and in situ hybridization techniques (Hassaname et al, 1993(Hassaname et al, , 1994Iannuzzi et al, 1997a-d). Furthermore, the difficulty in clearly identifying small acrocentric chromosomes, especially when banding techniques are applied with contracted chromosome preparations, lends greater importance to the ZOO-FISH analysis in river buffalo (Bubalus bubalis, BBU) chromosomes owing to the presence of marker chromosome pairs involving small, disputed cattle (Bos taurus, BTA) chromosomes in the standardized nomenclatures (Iannuzzi, 1996).…”
mentioning
confidence: 99%